Mechanisms of electrical polarization of disordered systems based on Al-substituted LiFe-oxospinel - A.V. Vakalyuk; V.M. Vakalyuk; M.I. Hasiuk; I.M. Hasiuk (Фізика і хімія твердого тіла, 2021)
The temperature-frequency dependences of the dielectric  permittivity and conductivity of Li2O-Fe2O3-Al2O3 ceramics in the temperature range of 298-648 K were obtained by impedance spectroscopy. Their analysis indicates the presence of a fractal-like structure in the studied samples, the effect of which is manifested at low temperatures. To study the phenomenon of electric polarization associated with this structure, we used the generalized law of Jonscher. A significant dependence of the dispersion of dielectric and conductive properties of these spinel ceramics on the temperature and aluminum content in them was revealed.